Profile of diabetic complications amongst diabetics attending internal medicine outpatient department and family medicine outpatient department in Dora Nginza Hospital, PE hospital complex - Ajudua, Emmanuel Enuagwuna (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MFamMed)--Stellenbosch University, 2015.